Use of traditional and complementary medicine and its associated factors among knee osteoarthritis patients in outpatient clnic, Hospital Universiti Sains Malaysia - Shafii, Nik Abdul Hafiiz N (2016)
Introduction: Osteoarthritis is the commonest arthritis worldwide especially in elderly. It ranks among the top ten causes of disability worldwide. The current management of Osteoarthritis does not provide definitive cure, however it was able to control pain, improved function and overall quality of life. Other than conventional treatment, some patients opted for traditional and complementary medicine (TCM) to treat the disease. Some of them use it alone however most of the patient combine both the conventional and TCM. Even though TCM is widely used, many of its marketed products were questionable in term of quality, efficacy, content and safety. There are many unregistered product which found to be contaminated with controlled drugs and poisons such as steroid, hormones, antihistamine and heavy metal which can cause a lot of unwanted effect and complication. Objectives: To determine the proportion of knee Osteoarthritis patient at HUSM outpatient clinic who uses traditional and complementary medicine (TCM) for their knee Osteoarthritis and its associated factors. Methodology: This study is a cross sectional study. 214 numbers of patients were involved in this survey. Convenience sampling method was applied to select participants who attended outpatient clinic in HUSM (Klinik Rawatan Keluarga) from May 2013 to October 2013. First, participants were interviewed to get the sociodemographic characteristics, clinical history and history of TCM use for knee osteoarthritis. After that, patients were given a questionnaire which is validated Malay version of Western Ontario and McMaster Universities Arthritis Index (WOMAC) to be self-administered. This questionnaire was used to assess the severity of knee osteoarthritis in term of pain, stiffness and disturbances in daily activity. The data was analyzed using the descriptive statistic and multiple logistic regressions Result: This study showed that the proportion of knee Osteoarthritis patient attended HUSM out-patient clinic that practice traditional and complementary medicine was 57.9%. Factors associated with TCM use in this study population was male (OR; 2.47, 95% CI: 1.28, 4.77), duration of knee Osteoarthritis (OR; 1.51, 95% CI: 1.03, 2.23) and severity of knee pain (OR; 2.57, 95% CI: 1.71, 3.86). Conclusion: The proportion of TCM use for knee Osteoarthritis in this population study was high. Clinicians should aware of its high usage. They should identify patients by asking them regarding use of TCM so further discussion and shared decision can be undertaken.